Outcome of an oral health outreach programme for preschool children in a low socioeconomic multicultural area - INGER WENNHALL (IAPD and Blackwell, 2008)
Despite a remarkable reduction in the prevalence of dental caries, childhood tooth decay is still a public health problem in developed and developing countries 1 . Oral health problems persist, particularly among poor and disadvantaged groups within the communities 2–4 , and similar disparities were also found in immigrant children living in Sweden 5–7 . Because childhood caries is a preventable disease, strategies based on restricting sugar and using fluoride in various preparations may help reduce this gap 8 . Other studies have pinpointed the effectiveness of early intervention with outreach activities from local health authorities 9